Two Phases of Labor Market Transition in Hungary: Inter-Sectoral Reallocation and Skill-Biased Technological Change - Gabor Kezdi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2002)
Hungary has been a front-runner in the transition to capitalism. It has also experienced exceptionally radical changes in employment and relative wages. One main feature of these changes is an enormous increase in the returns to skill. This paper argues that it is instructive to divide the process into two periods, divided by around the year 1995. The first period experienced major destruction of low-skilled jobs and large inter-sectoral reallocation, partly toward skill-intensive industries. Employment started to rebound in the second period, which has also seen a pervasive skill upgrade in all sectors. The skill premium in earnings started to grow even faster in the second stage because increasing demand for skill met a more and more inelastic supply in the short run. Long-run supply effects have been, however, strong as college enrollment rates soared. Introduction of new (foreign) capital seems to be a major factor behind increasing demand for skill. Foreign direct investment into Hungary was by far the largest among the transition countries until the late 1990's, but other Central-Eastern European countries started to catch up since. This suggests that the Hungarian experience might be helpful to predict labor market trends in other transition economies, especially those that attract significant foreign capital.
Keywords: 330